Servant leadership in the context of education: teachers as servant leaders with emphasis on individual development - Labib, Mariam Gamil (AUC Knowledge Fountain, 2015)
This study focuses on individual development as one of the characteristics of Servant Leadership. This is an attempt to attract more attention to Servant Leadership in the context of education as the study argues that teachers, with servant leadership behaviors, can enhance students’ individual development. The study pointed out Servant Leadership behaviors which relate to individual development in the non-fiction book “The Freedom Writers Diary” by Erin Gruwell, this book is the real story of a teacher who changed lives and made a difference. The study also traced students’ character qualities that can be attributed to having Ms. Gruwell as their teacher. The study sought to answer the following research questions: (a) What Servant Leadership behaviors for individual development can be traced in the book “The Freedom Writers Diary” by Erin Gruwell? (b) What character qualities in Erwin Gruwell students’ diary entries can be attributed to her influence as a teacher? A qualitative content analysis was conducted where coding of data was done according to themes and meanings interpreted from the text. Servant Leadership behaviors for individual development were pointed out in the lives of Jesus Christ and Gandhi who are considered role model servant leaders and also from the writings of the scholars who wrote about Servant Leadership. Then, those same behaviors were drawn from the non-fiction book “The Freedom Writers Diary”. Nine Servant Leadership behaviors were pointed out and listed as nine data codes derived from the analysis, in addition to nine respective character qualities drawn from the students’ diary entries included in the book. The study concluded that Servant Leadership can develop students’ characters and help them achieve better academic results; thus, Servant Leadership behaviors need to be a part of teacher preparation and evaluation. Moreover, more research is needed on Servant Leadership in the context of education.